The Effect of Constraint-Induced Movement Therapy Combined With Repetitive Transcranial Magnetic Stimulation on Hand Function in Preschool Children With Unilateral Cerebral Palsy: A Randomized Controlled Preliminary Study - Wu, Qianwen; Peng, Tingting; Liu, Liru; Zeng, Peishan; Xu, Yunxian; Yang, Xubo; Zhao, Yiting; Fu, Chaoqiong; Huang, Shiya; Huang, Yuan; Zhou, Hongyu; Liu, Yun; et al. (Frontiers in Behavioral Neuroscience, 2022)
Constraint-induced movement therapy (CIMT) combined with repetitive transcranial magnetic stimulation (rTMS) have been showed great potential in improving function in school children with unilateral cerebral palsy attributed to perinatal stroke. However, the prospect of application in preschool children with UCP attributed to various brain disorders remains unclear. In this prospective, assessor-blinded, randomized controlled study, forty preschool children with UCP (aged 2.5-6 years) were randomized to receive 10 days of CIMT combined with active or sham rTMS. Assessments were performed at baseline, 2 weeks and 6 months post-intervention to investigate upper limb extremity, social life ability, perceived changes by parents and motor evoked potentials. Overall, thirty-five participants completed the trial. The CIMT plus active stimulation group had greater gains in the affected hand function (range of motion, accuracy and fluency) than the CIMT plus sham stimulation group (P<0.05), but there was no significant difference in muscular tone, social life ability and perceived changes by parents between the two groups (P>0.05). In addition, there was no significant difference in hand function between children with and without motor evoked potential (P>0.05). No participants reported severe adverse events during the study session. In short, the treatment of CIMT combined with rTMS is safe and feasible for preschool children with UCP attributed to various brain disorders. Randomized controlled studies with large samples and long-term effects are warranted.